(untitled) (Journal of Bio-Science, 2015)
Context: To analyze the effect of sowing dates and weeding treatments on growth attributes such as total dry matter (TDM), leaf area index (LAI), net assimilation rate (NAR), crop growth rate (CGR), leaf area ratio (LAR) of three rapeseed (Brassica campestris L.) Objectives: The objective of the study was to identify the growth in relation to sowing dates and weed competition and identify the weeding number for better growth of rapeseed. Materials and Methods: This investigation was arranged as factorial experiment based on the split-split plot design with three replications. Four sowing dates were including 18 October (S1), 12 November (S2), 17 November (S3) and 3 December (S4) and three weeding treatments were no weeding (W0), one hand weeding (W1) and two hand weeding (W2) and three varieties viz., BINA Sarisha-5, BINA Sarisha-6 and BARI Sarisha-14 were investigated. Results: The results showed that, TDM, LAI, CGR, NAR and LAR were affected by sowing date and weeding treatments. The highest TDM, LAI and CGR were obtained in the first sowing and two weedings treatment. The highest NAR was found in S2 plants and W0 treatment. The highest LAR was found in S2 plants and W1 treatment. Conclusion: The results obtained in this study suggest that the first sowing and two weeding treatments are superior for the production of rapeseed. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22519 J. bio-sci. 21: 51-59, 2013